2008
DOI: 10.1007/s12192-008-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of heat-shock protein (HSP) 90 expression in acute myeloid leukemia cells

Abstract: The 90-kDa heat shock protein (HSP90) is implicated in the conformational maturation and stabilization of a variety of client proteins with receptor and signal transduction functions. The objective of this study was to assess its expression in primary acute myeloid leukemia (AML) cells and to evaluate its biological and clinical significance. The in vitro effects of 17-AAG, a selective inhibitor of HSP90, was also evaluated. Cells from 65 patients with newly diagnosed AML were studied. The expression of HSP90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…27,28 Interestingly, several genes flanking the integration sites, such as SOCS1, JARID2, PTPRE, HSP90, GADD45, MGAT5, PP2R5C or MN1, have been previously linked to carcinogenesis (Table 1). [29][30][31][32][33] The integration near the MN1 locus resulted in significantly increased levels of mRNA expression (Figure 1a). Interestingly, the MN1 gene locus has been previously reported as a recurrent integration site in mouse models of human hematological malignancies induced by retroviral oncogene expression such as NUP98-HOXD13 or mutated AML1.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interestingly, several genes flanking the integration sites, such as SOCS1, JARID2, PTPRE, HSP90, GADD45, MGAT5, PP2R5C or MN1, have been previously linked to carcinogenesis (Table 1). [29][30][31][32][33] The integration near the MN1 locus resulted in significantly increased levels of mRNA expression (Figure 1a). Interestingly, the MN1 gene locus has been previously reported as a recurrent integration site in mouse models of human hematological malignancies induced by retroviral oncogene expression such as NUP98-HOXD13 or mutated AML1.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 is a conserved molecular chaperone that targets specific client proteins involved in signal transduction, protein refolding, protein degradation, etc. (Pratt and Toft, 2003;Flandrin et al, 2008;Zhao et al, 2005;Jackson, 2013). For example, it has been reported that Hsp90 can bind to Akt to protect it from phosphatase 2A (PP2A)-catalysed dephosphorylation and to regulate the kinase activity (Sato et al, 2000;Basso et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Extensive preclinical studies have examined this chaperone as a potential new drug target in hematologic malignancies. [3][4][5][6][7] Among the more than 80 currently identified Hsp90 client proteins there are several kinases involved in myeloid neoplasms, including Bcr/abl, 8,9 Flt3, 4,10,11 and c-Kit, 12 as well as the anti-apoptotic kinase Akt. 13,14 When Hsp90 is inhibited, these polypeptides and other Hsp90 clients fail to fold properly during synthesis and, as a consequence, become less abundant as mature molecules turn over.…”
Section: Introductionmentioning
confidence: 99%